(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Acute coronary syndrome (ACS) is a term that encompasses both unstable angina and myocardial infarction (MI) with or without ST-segment elevation. “It is a life-threatening disorder that remains a source of high morbidity and mortality despite advances in treatment. “Risk assessment done by using risk factors and risk markers. “One of the emerged risk markers is high circulating level of PPAR-γ (a potentially important transcription factor). “This study represents a try to evaluate the role of this analyte as a risk biomarker for future cardiovascular events, and evaluation of PPAR-γ as a possible diagnostic biomarker for MI. “It was a case –control study enrolled 160 subjects; 80 patients diagnosed as ACS patients by expert physicians. “An equivalent age and sex matched population without coronary disease with similar risk factors considered a control group. Serum levels of PPAR-γ were measured by using ELISA technique, cTpI was investigated by qualitative membrane- based immunoassay. “Independent sample t-test was used to compare means between two groups. “ANOVA were used to compare means between different groups, p value ≤ 0.05 is significant. “There were significant differences in mean serum levels of PPAR-γ, by patients and control. “There was a significant difference in PPAR- γ serum levels between positive and negative cTpI groups. “There was an insignificant difference in PPAR- γ level among different ECG finding groups. “Circulating level of PPAR- γ seems to be used as a risk biomarker for ACS, it is suggested that it could be used as a diagnostic biomarker for MI.